Usage of Chelating Gels in Root Canal Preparation: A Survey of Australian Clinicians - Patricia P. Wright; Elise S. Diamond; Ove A. Peters (MDPI AG, 2024)
Chelating gels may initially assist in root canal preparations to help establish a glide path. While irrigation surveys have investigated liquid chelators and gels to a minor extent, no endodontic survey has focused on EDTA gels and why clinicians use them. All 395 members of the Australian Society of Endodontology (ASE) were emailed an 11-question survey concerning chelation gel usage via Qualtrics. Paper copies were also distributed at ASE events. Descriptive statistics were performed for practitioner and chelating gel data. Cross-tabulations of the practitioner type with the case percentage usage of gels were analyzed with the chi square test (adjusted p value < 0.0083). The overall response rate was 181/395 (46%). For 174 eligible responses, those who never/rarely used a gel were as follows: endodontic residents 12/14 (86%), endodontists 53/71 (75%), general dentists 39/86 (45%), and other members 0% (0/3). Most gel users said that gels helped establish a glide path. Those who never/rarely used chelating gels commented that they held no benefits over liquid EDTA. Endodontists were less likely to use a chelation gel than general dentists (p < 0.0083). Older clinicians had higher gel usage than younger ASE members (p < 0.0083), indicating a possible trend to diminished gel usage over time amongst ASE members. In conclusion, most ASE members find no need for a chelating gel, raising questions about their clinical effectiveness. Studies would therefore be warranted to investigate gel efficacy and improved clinical outcomes.